Analysis of Dynamics Characteristic of Ring Chain Under Transmission Fault Loading - Song Ruihan; Xue He; Cui Yinghao; Wang Ting; Li Kai (Jixie chuandong)
Aiming at the transient impact of the abrupt load on the ring chain under the fault of the scraper conveyor chain jammed,taking the Φ18 mm×64 mm C class mining ring chain as the research object,by using the ANSYS/LS-DYNA finite element software,the nonlinear chain contact dynamics analysis under the condition of the chain jammed is performed,the change law of the acceleration,velocity,energy and contact force of the ring chain and the main position of the ring chain damage are obtained. A theoretical basis for researching the damage mechanism of mining ring chain transmission under the condition of fault is provided.